Про можливість “сухого” тертя у надплинному Не4 - Tomchenko, M.D. (Publishing house "Academperiodika", 2022)
A possible microscopic explanation for the exhaustion of ρs in helium-II at the wall at T > Tc ~ 0.5÷1 K has been proposed, and a possibility for the "dry" friction to exist in He-II at T ≤ Tc has been predicted. Both effects are related to the fact that the energy of 2D-rotons is lower by 2~K than that of 3D-rotons, so that the wall is a potential well for the latter.